Saudi Arabia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2017)
This paper assesses the stability of Saudi Arabia's financial system as a whole. Banks-the core of the Saudi financial system-remain liquid and resilient. Stress tests show that most banks, including all systemically important banks, would be able to continue operating and meeting regulatory capital requirements in the event of additional severe economic shocks, characterized by oil prices falling substantially below current levels. Despite the recent liquidity challenges, all banks would also be able to cope with additional adverse liquidity shocks. The authorities' ambitious agenda for improving macro- and microprudential financial sector oversight should be fully implemented and, in some cases, enhanced and further refined.